Impacts of Climate Change and Land Use Change on Streamflow: A Case of Seti Gandaki Watershed, Nepal - Baral, Kushal; Pandey, Vishnu Prasad; Pradhan, Ananta Man Singh; Khanal, Avishek (Journal of Sustainability and Environmental Management, 2023)
Recent research and IPCC reports extensively document the varied effects of climate change on basins worldwide. This study evaluates the impact of climate change and land use change on the Seti-Gandaki watershed’s hydrological regime of Nepal. Using a calibrated hydrological SWAT model, forced with climate scenarios (SSP245 and SSP585), the study projects increased precipitation (2-129% and 3-139%) and a warming trend in temperature. Streamflow at the watershed’s outlet is expected to rise (up to 49% in monsoon, 96% in winter in SSP245; up to 61% in monsoon, 89% in winter in SSP585), with increased flow extremes, potentially leading to floods and landslides. The combined impacts project a 52-125% increase in streamflow in SSP245 and a 100-136% increase in SSP585, attributed to the shift from rural to urban settlements. These findings provide crucial insights for water resource planners and managers to develop location-specific strategies for sustainable water resource use in the Seti-Gandaki Watershed.